Synthesis, characterization and investigation of the photophysical and photochemical properties of highly soluble novel metal-free, zinc((II)), and indium((III)) phthalocyanines substituted with 2,3,6-trimethylphenoxy moieties - ALTUN, SELÇUK; ODABAŞ, ZAFER (ROYAL SOC CHEMISTRY, 2015)
This work presents the synthesis and characterization of metal-free, zinc((II)), and indium((III)) acetate phthalo-cyanines substituted with 2,3,6-trimethylphenoxy groups at the peripheral and non-peripheral positions. The photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of these novel phthalocyanines and un-substituted zinc((II)) and indium((III)) acetate phthalocyanines were investigated in dimethylformamide solution. The effects of the types of substituents and their positions and the variety of central metal ions on the phthalocyanine core on their spectroscopic, photophysical and photochemical properties were also determined. The studied 2,3,6-trimethylphenoxy substituted metal-free, zinc((II)) and indium((III)) acetate phthalocyanines especially indium((III)) acetate derivatives exhibited appropriate photophysical and photochemical properties such as high singlet oxygen generation and these phthalocyanines can be potential Type II photosensitizers for photodynamic therapy in cancer applications.
Keywords: SILICON PHTHALOCYANINES; ELECTRONIC ABSORPTION; DERIVATIVES; BEHAVIOR; PHENOXY; TETRA